Hierarchy of Meaning in Interpretation:Sharia, Customary, and Linguistic Meanings in the Digital Literacy Era - Ariesta Nadya Alfadhela; Sutrisno Hadi; Pathur Rahman (PT. Education Research Center, 2025)
This study aims to analyze the hierarchy of meaning in the interpratation of the Qur’an, focusing on the relationship between syar’i meaning (legal/religious), ‘urf meaning (customary), and linguistic meaning in the context of digital literacy. The research method used is a qualitative literature review with a descriptive-analytical approach. Data were collected from primary and secondary sources, including classical and contemporary books as well as acrredited sinta journals. The resultsshow that there is a dynamic hierarchy between these three meanings, where syar’i meaning serves as the primary foundation, while ‘urf and linguistic meanings function as contextl mediators in understanding the text. In the digital era, the interaction between these three meanings faces challenges, such the spread of literal interpretations that ignore context and the dominance of popular narratives that are often not based on strong academic foundations. This study concludes that a holistic and contextual approach is eesential in interpreting the Qur’an to maintain the relevance of its teachings amids the rapid flow of digital information